Antibiotic Use and Antimicrobial Resistance: A Global Public Health Crisis - Ana Estany-Gestal; Angel Salgado-Barreira; Juan Manuel Vazquez-Lago (MDPI AG, 2024)
The discovery of antibiotics revolutionized modern medicine, effectively treating bacterial infections that were once fatal [...]